John Knox and education - Duncan, Graham (HTS teologiese studies, 2017)
John Knox the 16th century Scottish reformer made a lasting impact on the Scottish nation in the fields of society, politics, church and education. He is remembered mainly for his reform of the church but he also made a significant contribution to the reform of education, which has lasted until the present day and has impacted on other contexts. Although much of his vision was not realised during his lifetime, his mission continued nonetheless. He was a product of the late Medieval age and his transformation was completed by his experience alongside John Calvin in Geneva. This was then contextualised in his own Scottish situation. Here we examine his work in the field of education with particular reference to the First Book of Discipline. The outcome of his labours was a compulsory, universal system of free education, which involved character formation and enabled all to achieve the limit of their potential.